2021
DOI: 10.3390/jpm11060504
|View full text |Cite
|
Sign up to set email alerts
|

Improved Models of Human Endometrial Organoids Based on Hydrogels from Decellularized Endometrium

Abstract: Organoids are three-dimensional (3D) multicellular tissue models that mimic their corresponding in vivo tissue. Successful efforts have derived organoids from primary tissues such as intestine, liver, and pancreas. For human uterine endometrium, the recent generation of 3D structures from primary endometrial cells is inspiring new studies of this important tissue using precise preclinical models. To improve on these 3D models, we decellularized pig endometrium containing tissue-specific extracellular matrix an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…We derived endometrial organoids from healthy women, as previously described [61,64], and for the first time, have reproducibly established organoids from endometria of adenomyosis patients. Organoids recapitulated the molecular signatures of in vivo endometrial glands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We derived endometrial organoids from healthy women, as previously described [61,64], and for the first time, have reproducibly established organoids from endometria of adenomyosis patients. Organoids recapitulated the molecular signatures of in vivo endometrial glands.…”
Section: Discussionmentioning
confidence: 99%
“…To verify that Control-and adenomyosis (Adeno) derived-organoids reproduced biological and pathological features of the native tissue, organoids were fixed, paraffin embedded [64], and cut into 4-µm sections. Periodic acid-Schiff (PAS) (glycogen secretion) (Sigma-Aldrich, St. Louis, MO, USA, 395B) staining was performed according to manufacturer's protocol.…”
Section: Immunohistochemical (Ihc) and Immunofluorescence (If) Charac...mentioning
confidence: 99%
“…Though efforts to generate Matrigel alternatives to culture endometrial cells have been presented 8589 , we report a fully synthetic hydrogel formulation that supports the long-term embedded culture of both primary EEOs and ESCs in 3D. Our previous work using endometrial cell lines identified that the fibronectin-mimetic (PHSRN-K-RGD) peptide supported the culture of endometrial fibroblasts in a synthetic hydrogel.…”
Section: Discussionmentioning
confidence: 93%
“…The solubilized dECM is then neutralized to physiologic pH, salt concentration and temperature dominated by collagen assembly ( 26 ). dECM-based hydrogels have been used for the culture of brain ( 28 , 29 ), endodermal ( 30 , 31 ), islet ( 32 , 33 ), retinal ( 34 ), testicular ( 35 ), and endometrial ( 36 ) organoids. Additionally, Giobbe et al ( 31 ) demonstrated that endoderm-derived organoids, including small intestinal, gastric, hepatic, and pancreatic organoids, could be cultured in the decellularized porcine small intestine mucosa/submucosa.…”
Section: Decellularized Tissue-derived Scaffoldsmentioning
confidence: 99%